Coinfection of malaria and scrub typhus in a toddler: First report from South India - Nandini Vasudevan; Sawantharia Jaganathan; Priya Jose; Peter Prasanth Kumar Kommu (Journal of Current Research in Scientific Medicine)
Tropical infections are common in South Asia, including India. However, coinfections among the different diseases are rare in children. We report a case of malaria-scrub typhus coinfection in a toddler from South India. A 3-year-old boy presented with fever. He was pale, dull-looking and had hepatosplenomegaly.. There was mild leukocytosis with positive C reactive protein. Rapid malarial antigen was positive, and started on antimalarial therapy. Fever was persisting after 48 h and doxycycline was started. Scrub typhus immunoglobulin M was positive. He responded dramatically to doxycycline, and in 24 hours, he became afebrile. The prevalence of this coinfection was studied by Wilairatana et al. in 2021 and showed a low prevalence of 0%–1%. Our case is unique and rare as this has not been reported in a toddler. Children with acute undifferentiated fever which is not responding to therapy within 48 hours must be investigated for concurrent infection.